Hysteretic Implications for Graded Bed Load Sediment Transport in Symmetrical Hydrograph Flows - Wang, Le; Wang, Dayu; Cuthbertson, Alan; Zhong, Deyu; Pender, Gareth (Frontiers in Environmental Science, 2021)
Differential parametric values associated with bed load sediment transport, that result at the same discharge levels on the rising and falling limbs of a flood hydrograph, are usually defined as bed load hysteresis. This hysteresis in bed load sediment transport rates is of considerable interest in the field of fluvial hydraulics. Within this study, a series of well-defined, symmetrical hydrograph flows are generated over a graded, mobile sediment bed to fully examine the hysteresis of the resulting bed load sediment transport in terms of the threshold of motion, and differential bed load transport rates and bed load yields during the hydrographs. The experiments are conducted in a titling flume without sediment supply specified at the upstream inlet, thereby representing typical river reach conditions immediately downstream of a dam that are exclusively subject to net in-channel bed degradation from sediment transport initiated during flood events. Our results show that the fractional bed load transport of defined fine, medium and coarse size classes within the graded sediment bed generally display clockwise, no/mixed and counter-clockwise hysteresis patterns, respectively, with clockwise hysteresis most commonly found for the coarse size class mobilised by hydrographs with long durations. By contrast, counter-clockwise hysteresis is usually observed for fine size class transported by hydrographs with short durations. Accordingly, the corresponding reference stresses for each size class vary between different hydrographs and are primarily controlled by the hydrograph flashiness (i.e. unsteadiness) and magnitude (i.e. total water work). Moreover, it is shown that the hysteresis effect, particularly for those size classes and hydrograph combinations that result in clockwise and counter-clockwise behaviour, should be fully accounted for when reproducing bed load transport rates using separate-limb based method. Finally, we investigate the relative fractions of the overall bed load yields generated during the rising and falling limbs of all symmetrical hydrographs (i.e. the bed load yield ratio), which are found to be primarily dependent on bed load transport hysteresis. Finally, the relationship between the bed load yield ratio and the ratio of reference stresses for the fractional sediment motion of each size class on both limbs is found to follow a power law.